KONSTRUKSI PEMIKIRAN TASAWUF WUJUDIYAH DALAM NASKAH AMBULUNG DI KALIMANTAN SELATAN - Nur Kolis (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
This article aims to refute theÂ opinionÂ that states,Â SufismÂ as aÂ static construction of orthodox thought.Â It is doneÂ by looking deeply into the dynamic dimensions of Sufism andÂ capturingÂ the side of transformation that occurs, as seen in theÂ Ambulungmanuscript in South Kalimantan.Â StartingÂ from three main issues,Â relatedÂ to;Â mapping the contextual (transformative) dimensions of Sufism in theÂ AmbulungÂ manuscript;Â variousÂ factors influencing the transition of Sufism understanding construction in theÂ AmbulungÂ manuscript; and the construction process of Sufismâ€™s teaching conceptÂ in theÂ Ambulungmanuscript, the results of the study show that theÂ Sufismâ€™sÂ teaching in theÂ AmbulungÂ manuscript is aÂ wujudiyyahÂ concept which isÂ full of controversy inÂ theÂ Islamic history. ThisÂ manuscriptÂ isÂ only studiedÂ by theÂ sirÂ (special or limited)Â community, whose participants are limitedÂ forÂ Sufism teachers. Not for the publicÂ audience, becauseÂ of itsÂ teachings are considered potentiallyÂ beingÂ misunderstood. The teachings contained in thisÂ manuscript, indirectlyÂ persuade peopleÂ to dynamically think moderately,through understandingÂ tauhidÂ wujudiyyahÂ whichÂ are tolerant and opennessÂ toÂ the diversity.